Hungarian Monitoring, 10 November 1990 . [Magyar rádiófigyelő], 1990. november 10 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Gorbachev's German visit - 100,000 soldiers ordered to be stationed in the Persian Gulf - Baker's talks with the French Domestic Affairs: - Árpád Göncz in Tokyo - Fate of the Hungarian Socialist Party after Pozsgay's departure - Gyula Thürmer returns from Beijing Economy: - On the economic possibilities of the World Exposition - 40% inflation possible - Complications in distribution of student grants Külpolitika: - Gorbacsov németországi látogatása - Százezer katona behajózási parancsa az Perzsa-öböl térségébe - Baker tárgyalása a franciákkal Belpolitika: - Göncz Árpád Tokióban - Az MSZP sorsa Pozsgay kilépése után - Thürmer Gyula hazatért Pekingből Gazdaság: - A világkiállítás gazdasági lehetőségeiről - 40%-os infláció lehet - Bonyodalom a hallgatói ösztöndíjak kiosztásánál